Evolutionary and genomic insights into meningococcal biology - Bratcher, H; Bennett, J; Maiden, M (Future Medicine, 2012)
Epidemic disease caused by Neisseria meningitidis, the meningococcus, has been recognized for two centuries, but remains incompletely controlled and understood. There have been dramatic reductions in serogroup A and C meningococcal disease following the introduction of protein-polysaccharide conjugate vaccines, but there is currently no comprehensive vaccine against serogroup B meningococci. Genetic analyses of meningococcal populations have provided many insights into the biology, evolution and pathogenesis of this important pathogen. The meningococcus, and its close relative the gonococcus, are the only pathogenic members of the genus Neisseria, and the invasive propensity of meningococci varies widely, with approximately a dozen 'hyperinvasive lineages' responsible for most disease. Despite this, attempts to identify a 'pathogenome', a subset of genes associated with the invasive phenotypes, have failed; however, genome-wide studies of representative meningococcal isolates using high-throughput sequencing are beginning to provide details on the relationship of invasive phenotype and genotype in this fascinating organism and how this relationship has evolved.